Employment as a Price or a Prize of Equality: A Descriptive Analysis - Barth, Erling; Moene, Karl Ove (Nordic Journal of Working Life Studies, 2012)
To put Scandinavian employment in perspective, we ask whether wage compression hampers employment rates, or not. We answer by reviewing the most important theoretical arguments and the most informative regularities across countries with different wage distributions. The pattern seems to be that countries with compressed wage distributions tend to have higher employment, and countries with higher wage inequality tend to have lower employment. This also holds when we consider the rate of labor force participation. In line with the theoretical arguments, coordination in wage bargaining seems to contribute to both employment expansion and wage compression. There is a clear positive correlation between coordination and employment even when we control for inequality, country, and year-specific effects.